Antimicrobial resistance in community-acquired enteric pathogens amongst children ≤10-years in low- and middle-income countries: a systematic review and meta-analysis - Okumu, Noah O.; Muloi, Dishon M.; Moodley, Arshnee; Watson, J.; Kiarie, Alice; Ochieng, Linnet; Wasonga, Joseph O.; Mutisya, Christine; Alumasa, Lorren; Ngeranwa, J.J.N.; Cumming, O.; Cook, Elizabeth A.J. (Frontiers Media, 2025)
Introduction: Antimicrobial resistance (AMR) is a global health priority. This systematic review summarizes the prevalence of AMR in enteric pathogens originating from the community, specifically among ≤10-year-old children in low-and middle-income countries (LMICs). In addition, it presents the proportions of pooled resistance in Campylobacter spp., Escherichia coli, Shigella spp., and Salmonella spp. (CESS) to clinically relevant antibiotics.